Levels and associated factors for early cessation of EBF among under six month children in Ethiopia - Fassikaw Kebede Bizuneh; Tsehay Kebede Bizuneh (Cogent Public Health)
Exclusive breastfeeding is recognized as the safest and healthiest feeding choice for infants in their first six months of life. Premature discontinuation can lead to risks of malnutrition, infections, impaired brain development, and increase the maternal susceptibility to breast and ovarian cancers. This study aimed to identify Multi-level risk factors for early termination of EBF for infants. A weighted sample of 1626 (Wt = 100%) mothers with infants was included in the final analysis. A mixed-effects multilevel logistic regression model employed to identify factors contributing to premature cessation. Intra-cluster correlation median odds ratio, and proportional change in variance used to assess random effects. The average age of women with paired infants was 27.4 (±6.25) years, while the mean age of infants was 4.79 (±2.34) months. The estimated national rate of early termination of exclusive breastfeeding was 15.8% (95% CI: 14.11–17.66). The final multilevel logistic regression model indicated that certain factors were significant predictors for early cessation of Exclusive Breastfeeding (EBF) in Ethiopia. These included infant age 5–6 months (Adjusted odds ratio = 2.14), male infants (Adjusted odds ratio = 0.56), delayed initiation of breastfeeding (Adjusted odds ratio = 156.8), infant co-morbidities (Adjusted odds ratio = 2.3), maternal education level (Adjusted odds ratio = 3.16), lowest wealth index (Adjusted odds ratio = 3.2), and peripheral regions (Adjusted odds ratio = 2.12). This study found that one in every six lactating women discontinued EBF before their infants reached six months of age.